Adenovirus-mediated hAQP1 expression in irradiated mouse salivary glands causes recovery of saliva secretion by enhancing acinar cell volume decrease - Teos, L Y; Zheng, C-Y; Liu, X; Swaim, W D; Goldsmith, C M; Cotrim, A P; Baum, B J; Ambudkar, I S (Gene therapy, 2016)
Head and neck irradiation (IR) during cancer treatment causes by-stander effects on the salivary glands leading to irreversible loss of saliva secretion. The mechanism underlying loss of fluid secretion is not understood and no adequate therapy is currently available. Delivery of an adenoviral vector encoding human aquaporin-1 (hAQP1) into the salivary glands of human subjects and animal models with radiation-induced salivary hypofunction leads to significant recovery of saliva secretion and symptomatic relief in subjects. To elucidate the mechanism underlying loss of salivary secretion and the basis for AdhAQP1-dependent recovery of salivary gland function we assessed submandibular gland function in control mice and mice 2 and 8 months after treatment with a single 15-Gy dose of IR (delivered to the salivary gland region). Salivary secretion and neurotransmitter-stimulated changes in acinar cell volume, an in vitro read-out for fluid secretion, were monitored. Consistent with the sustained 60% loss of fluid secretion following IR, a carbachol (CCh)-induced decrease in acinar cell volume from the glands of mice post IR was transient and attenuated as compared with that in cells from non-IR age-matched mice. The hAQP1 expression in non-IR mice induced no significant effect on salivary fluid secretion or CCh-stimulated cell volume changes, except in acinar cells from 8-month group where the initial rate of cell shrinkage was increased. Importantly, the expression of hAQP1 in the glands of mice post IR induced recovery of salivary fluid secretion and a volume decrease in acinar cells to levels similar to those in cells from non-IR mice. The initial rates of CCh-stimulated cell volume reduction in acinar cells from hAQP1-expressing glands post IR were similar to those from control cells. Altogether, the data suggest that expression of hAQP1 increases the water permeability of acinar cells, which underlies the recovery of fluid secretion in the salivary glands functionally compromised post IR.